The Casebook of Sherlock Holmes & His Last Bow - Doyle, Arthur Conan (Noida(up): Om books International, 2019.)
This collection includes perhaps the most intriguing, almost Gothic, stories ever written about the detective and his companion and truly tests their brain and brawn. From murderous revenge to mutilation, vampires, and more strange occurrences, this collection explores a variety of themes and modes of narration that mark a break from the earlier stories while remaining as riveting. Adapted to film, television, and radio several times over, these stories truly remain Evergreen.
The Originals
Keywords: Classics